(untitled) (Clinics, 2012)
OBJECTIVE: This study sought to outline the clinical and laboratory characteristics of minimal change disease in adolescents and adults and establish the clinical and laboratory characteristics of relapsing and non-relapsing patients. METHODS: We retrospectively evaluated patients with confirmed diagnoses of minimal change disease by renal biopsy from 1979 to 2009; the patients were aged >;13 years and had minimum 1-year follow-ups. RESULTS: Sixty-three patients with a median age (at diagnosis) of 34 (23-49) years were studied, including 23 males and 40 females. At diagnosis, eight (12.7%) patients presented with microscopic hematuria, 17 (27%) with hypertension and 17 (27%) with acute kidney injury. After the initial treatment, 55 (87.3%) patients showed complete remission, six (9.5%) showed partial remission and two (3.1%) were nonresponders. Disease relapse was observed in 34 (54%) patients who were initial responders (n = 61). In a comparison between the relapsing patients (n = 34) and the non-relapsing patients (n = 27), only proteinuria at diagnosis showed any significant difference (8.8 (7.1-12.0) vs. 6.0 (3.6-7.3) g/day, respectively, p = 0.001). Proteinuria greater than 7 g/day at the initial screening was associated with relapsing disease. CONCLUSIONS: In conclusion, minimal change disease in adults may sometimes present concurrently with hematuria, hypertension, and acute kidney injury. The relapsing pattern in our patients was associated with basal proteinuria over 7 g/day.